Pendidikan Kesehatan dan Peningkatan Pengetahuan, Support Tentang Inspeksi Visual Asam Asetat Test Pada Komunitas Ibu Usia Reproduktif - Handayani, Sri; Nurlaeli, Nurlaeli; Sahalessy, Yona; Subani, Natalia Debi; Treasa, Adisty Dwi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Cervical cancer is a disease characterized by uncontrolled cell growth and abnormal cell spread. The leading cause of death in women is Cervical Cancer. One way to prevent cervical cancer is by conducting a Visual Inspection Acetic Acid Test on the cervix, this is a government recommendation to reduce cancer cases. The purpose of this community service activity is to increase the knowledge and motivation of participants, namely reproductive-age mothers, about the Visual Inspection Acetic Acid Test. The form of community service activities is through health education. The target of the activity is reproductive-age mothers who visit the Manisa Health Center, Manisa Village. The implementation time is May 24, 2023. The media used is leaflets. The evaluation method is a pretest and posttest regarding participants' knowledge of the Visual Inspection Acetic Acid Test. The instrument for evaluation is a questionnaire distributed before and after the health education activity. Community service activities through health education that have been carried out have a positive impact on knowledge and motivation about the Visual Inspection Acetic Acid Test in reproductive-age mothers at the Manisa Health Center, Manisa Village. It is expected that participants can further increase their awareness and motivation to be able to carry out IVA examinations.